2021
DOI: 10.3390/cells10030646
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ku70 Domain-Specific Interactors Using BioID2

Abstract: Since its inception, proximity-dependent biotin identification (BioID), an in vivo biochemical screening method to identify proximal protein interactors, has seen extensive developments. Improvements and variants of the original BioID technique are being reported regularly, each expanding upon the existing potential of the original technique. While this is advancing our capabilities to study protein interactions under different contexts, we have yet to explore the full potential of the existing BioID variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 116 publications
0
14
0
Order By: Relevance
“…Finally, the biotinylation of the BioID2 fusion proteins was also tested, as described previously [ 8 , 9 ], and each of the BioID2 fusion proteins demonstrated robust biotinylation 24 h after 8 h of doxycycline induction, and only with the addition of supplemental biotin ( Figure 1 D).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Finally, the biotinylation of the BioID2 fusion proteins was also tested, as described previously [ 8 , 9 ], and each of the BioID2 fusion proteins demonstrated robust biotinylation 24 h after 8 h of doxycycline induction, and only with the addition of supplemental biotin ( Figure 1 D).…”
Section: Resultsmentioning
confidence: 98%
“…As expected, the vast majority of cells demonstrated consistent nuclear localization and the results also showed that most cells expressed the fusion proteins ( Figure 1 C). Our previous work with Ku70 using both BioID [ 8 ] and BioID2 [ 9 ] indicated that a C-terminal addition of the biotin ligase would not hinder Ku70 nuclear localization, function, or heterodimerization with Ku80.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, CCP6 did not co-immunoprecipitate PCM1 or PIBF1 ( Figure S4A,B ), suggesting that the interaction between CCP6 and PCM1 or PIBF1, if proven to be true, may be transient or weak. Thus, we performed a proximity ligation assay (PLA), an approach previously used to validate BioID screenings and with the potential to assess the presence and location of weak binary interactions that, otherwise, could not be detected by harsher methods such as co-immunoprecipitation [ 55 , 56 , 57 ]. In PLA, the two proteins under evaluation are targeted by primary antibodies raised in different species, and specific DNA probes are linked to the corresponding secondary antibodies (i.e., PLA probes), which will only be able to hybridize provided both proteins are in proximity ( Figure 4 E).…”
Section: Resultsmentioning
confidence: 99%